Maxillofacial Non-Hodgkin’s Lymphoma - Santan Reddy Muthyam; P. Surekha; Charan Paul Motupalli (New Frontiers in Medicine and Medical Research Vol. 12, 2021)
Morbidity and mortality are the devastating outcomes of noncommunicable diseases like cancer. Incidence of cancer has been growing globally due to consumption of tobacco, alcohol, radiation, chemicals, viral infections, obesity and immunosupression. Non-Hodgkin’s Lymphoma is one of the many cancers that humans suffer with. With the increasing number of health conditions that eventually lead to immunosupression and exposure to potential risk factors, the incidence of Non-Hodgkin’s Lymphoma has increased. It’s multivariate and misleading presentation in the head and neck region is a diagnostic nightmare. Early diagnosis is possible with critical evaluation of the presenting symptoms even in disseminated cases. Fine needle aspiration cytology should be unhesitently performed that may lead the physician in opting for more confirmative histological and radiological investigations. Standard therapeutic regimens seem to work well with patients diagnosed early, however risk of relapse looms over the future. The contents of this chapter focus on the maxillofacial and head and neck manifestations of Non-Hodgkin’s Lymphoma which are not frequently encountered.